2010
DOI: 10.1021/la100293s
|View full text |Cite
|
Sign up to set email alerts
|

ZnO Nanoparticles: Synthesis, Characterization, and Ecotoxicological Studies

Abstract: The potential ecotoxicity of nanosized zinc oxide (ZnO), synthesized by the polyol process, was investigated using common Anabaena flos-aquae cyanobacteria and Euglena gracilis euglenoid microalgae. The photosynthetic activities of these microorganisms, after addition of ZnO nanoparticles, varied with the presence of protective agents such as tri-n-octylphosphine oxide (TOPO) and polyoxyethylene stearyl ether (Brij-76) used to control particle size and shape during the synthesis. In the case of Anabaena flos-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
131
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 184 publications
(134 citation statements)
references
References 16 publications
3
131
0
Order By: Relevance
“…Indeed, the photosynthetic activity was found statistically decreased in the microalgae grown in both media since the first 24h of exposure to the ZnO nanoparticles, but there was a gradual negative trend along the days. This effect was already observed by Brayner et al [5], for their synthesized nanoZnO. The deregulation in the cells energetic metabolism can also be confirmed by the intracellular ATP content, a parameter related to the mitochondrial activity.…”
Section: Assessment Of the Factors Linked To The Toxicitysupporting
confidence: 72%
See 2 more Smart Citations
“…Indeed, the photosynthetic activity was found statistically decreased in the microalgae grown in both media since the first 24h of exposure to the ZnO nanoparticles, but there was a gradual negative trend along the days. This effect was already observed by Brayner et al [5], for their synthesized nanoZnO. The deregulation in the cells energetic metabolism can also be confirmed by the intracellular ATP content, a parameter related to the mitochondrial activity.…”
Section: Assessment Of the Factors Linked To The Toxicitysupporting
confidence: 72%
“…Although no zeta potential study was performed, which is a limitation of this study, previous works from our research group with ZnO from diverse synthesis routes showed that zero-point charge is generally expected to be around pH 9.0 [5,11]. According to these authors, this material tends to be slightly negative between pH 4 and 6, neutral between pH 8 and 10 and highly negative between pH 10 and 12.…”
Section: Zno Characterizationmentioning
confidence: 87%
See 1 more Smart Citation
“…For example, theoretically, a lipid-soluble synthetic dispersant could interact with the cell membrane (also lipophilic) to deliver more ENM to the test organism inadvertently, thus increasing the apparent toxicity of the test. In such circumstances, this additional effect on toxicity would not be evident in the dispersion agent control [32,33].…”
Section: Dispersing Agents and Solvent Controlsmentioning
confidence: 99%
“…The potential ecotoxicity of nanosized zinc oxide, synthesized by the polyol process, was investigated using common Anabaena flos-aquae cyanobacteria and Euglena gracilis euglenoid microalgae (72). Via addition of ZnO nanoparticles, the photosynthetic activities of these microorganisms varied with the presence of protective agents such as tri-octylphosphine oxide (TOPO) and polyoxyethylene stearyl ether (Brij-76) which is used to control particle size and shape during ZnO synthesis.…”
Section: Biocompatibility and Toxicity Aspects Of Zno Applicationsmentioning
confidence: 99%